2020
DOI: 10.1007/s11233-020-09061-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring doctorate holders’ perceptions of the non-academic labour market and reputational problems they relate to their employment

Abstract: Doctoral employment outside universities has been increasing, as universities cannot employ all doctorate holders. Nevertheless, it has been argued that the shift from doctoral programs to the non-academic labour market has been limited. In this qualitative study, more than 800 verbal answers given by doctorate holders to a pair of open-ended questions were content-analysed to explore doctorate holders’ perceptions of the non-academic labour market and the reputational problems they relate to their employment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
(82 reference statements)
0
2
0
2
Order By: Relevance
“…Harada et al (2021) found that most doctoral graduates in Japan pursue academic careers, and those who pursue non-academic careers often do so in fields related to their research areas. Based on a part of a larger research project conducted in Finland in 2018, a Finish team identified four reputational problems which doctorate holders related to employment: the oversupply problem, the overeducation problem, the consistency problem and the communication problem (Suomi et al, 2020).…”
Section: Huangmentioning
confidence: 99%
“…Harada et al (2021) found that most doctoral graduates in Japan pursue academic careers, and those who pursue non-academic careers often do so in fields related to their research areas. Based on a part of a larger research project conducted in Finland in 2018, a Finish team identified four reputational problems which doctorate holders related to employment: the oversupply problem, the overeducation problem, the consistency problem and the communication problem (Suomi et al, 2020).…”
Section: Huangmentioning
confidence: 99%
“…University graduates have been on the increase over the last few decades, with the number of doctorate holders growing fast (Auriol, 2016). For a long time, academia was the usual workplace for PhD holders, but doctoral graduates are increasingly employed in institutions and businesses outside academia (Passaretta et al, 2019; Steinþórsdóttir et al, 2019; Suomi et al, 2020).…”
Section: Doctorate Holdersmentioning
confidence: 99%
“…Muitos autores registraram evidências de sobrequalificação de Doutores em vários países GAETA;LAVADERA;PASTORE, 2017;GHOSH;GRASSI, 2020;SUOMI et al, 2020). As pessoas sobrequalificadas tendem a ter seus rendimentos reduzidos nos mercados, quando comparadas à casos de compatibilidade trabalhoeducação GAETA;LAVADERA;PASTORE, 2017;POULIAKAS, 2017).…”
Section: Crescimento E Os Desafios Dos Sistemas De Educação Doutoralunclassified
“…A oferta excessiva de doutores na economia significa que há mais doutores entrando no mercado de trabalho do que a demanda atual pelas habilidades dessa mão de obra pelas organizações. O excesso de doutores na economia está é parte das causas de um conjunto problemas de produtividade em empresas que contratam pessoas sobrequalificadas GAETA;LAVADERA;PASTORE, 2017;GERMAIN-ALAMARTINE, 2019;LEVECQUE et al, 2017;SUOMI et al, 2020).…”
Section: Gap Teórico E a Natureza Complexa Do Problemaunclassified